A silicon negative electrode binder for lithium-ion batteries based on functionalized sulfonated graphene

By using functionalized sulfonated graphene as a binder in lithium-ion batteries, the volume expansion and low conductivity of the silicon negative electrode material during charging and discharging are solved, and the electrochemical stability and cycle life of the battery are significantly improved.

CN119752327APending Publication Date: 2025-04-04SUZHOU JING TONG OPTRONICS TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411950750.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The huge volume expansion and low conductivity of the silicon anode material in lithium-ion batteries during charging and discharging lead to poor battery cycle life and low Coulomb efficiency, limiting the industrialization of silicon-based anodes.

Method used

Using a binder based on functionalized sulfonated graphene, the graphene oxide is sulfonated and modified to increase its interaction site with silicon powder particles, and the dispersion and stability of the binder are assisted by citric acid.

Benefits of technology

It significantly improves the electrochemical stability, cycle stability and lithium ion transmission capacity of lithium ion batteries, reduces the irreversible slippage of silicon particles during the circulation process, and extends the cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005214811710000011
    Figure HDA0005214811710000011
  • Figure HDA0005214811710000021
    Figure HDA0005214811710000021
  • Figure HDA0005214811710000031
    Figure HDA0005214811710000031
Patent Text Reader

Abstract

The present application relates to a lithium-ion battery silicon negative electrode binder based on functionalized sulfonated graphene, which comprises a sulfonated graphene oxide and silicon powder composite, wherein the sulfonated graphene raw material comprises graphene oxide and p-aminobenzenesulfonic acid. The present application has the effect of improving the electrochemical stability, cycle stability and lithium ion transmission capacity of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery binders, and in particular to a lithium-ion battery silicon negative electrode binder based on functionalized sulfonated graphene. Background Art

[0002] With the continuous development of science and technology and the rise of the new energy industry, people's requirements for energy storage materials are getting higher and higher, and the demand for energy storage devices with fast charging, high energy storage and stable performance is becoming more and more urgent. As a widely used energy storage device, lithium-ion batteries are favored by more and more people, and the research on various materials in lithium-ion batteries is becoming more and more in-depth. The commercially available graphite negative electrode is about to reach its theoretical capacity (372mAh / g), and it is urgent to find a new negative electrode material with a higher theoretical capacity. As the second most abundant element in the earth's crust, Si has an excellent theoretical specific capacity (4200mAh / g) and a suitable charge and discharge voltage. Its derivative SiO x It also has great potential in lithium storage.

[0003] Despite its many advantages, Si negative electrodes still have many problems. Due to the huge volume expansion (400%) of silicon during lithium insertion and removal, as well as its inherent low electrical conductivity and low ion conductivity, it also shows obvious disadvantages when used as a negative electrode material: First, as an electrode material, good electrical conductivity and ion conductivity are the prerequisites for obtaining excellent electrochemical performance, but Si is a semiconductor and does not have the ability to conduct electrons quickly. Secondly, the lithium insertion and removal of silicon during the charging and discharging process forms a lithium-silicon alloy with lithium ions. This lithium storage form not only brings high capacity, but also causes Si to show a huge volume expansion (about 300%) during repeated charging and discharging. The consequences are very obvious: the electrode material Si will be pulverized. Since silicon particles conduct electrons for the battery by attaching to the current collector copper foil, repeated volume expansion will cause silicon particles to detach from the current collector, thereby destroying the conductive network, and finally, forming an unstable and thick solid electrolyte interlayer (SEI). SEI is the organic and inorganic layer products produced by the decomposition of substances in the electrolyte during the first charge and discharge process of the electrode. These substances will be deposited on the electrode surface to form SEI. The moderate generation of SEI can protect the electrode, reduce the reaction between the electrode interface and the electrolyte, and reduce the consumption of the electrolyte. However, the continuous volume change of Si causes the electrode to continuously produce new surfaces, thereby increasing the contact between the new electrode surface and the electrolyte, and the SEI layer is also continuously produced. An overly thick and unstable SEI will consume lithium ions and electrolytes, thereby reducing the charge and discharge efficiency of the battery.

[0004] All of the above problems will lead to poor battery cycle life and low coulombic efficiency. Based on these problems, the industrialization of silicon-based negative electrodes is limited. At present, people are constantly improving silicon-based electrode materials through research on silicon electrode materials to adapt to the problems caused by volume expansion. For example, Si and graphite composite electrodes are used. The mechanical properties of graphite are stable and can withstand most of the stress during the Li deintercalation process, reducing the stress on silicon. Silicon derivatives such as SiO, SiO x The volume expansion effect they produce is lower than that of pure silicon materials. Although the above solutions can reduce the impact of volume expansion, they all reduce the proportion of Si in the active material, that is, they sacrifice the theoretical specific capacity of the material, and the problem of volume expansion still exists in SiO, SiO x It can be seen from the materials that using composite materials and silicon derivatives as ideal negative electrode materials for lithium-ion batteries is not the ultimate solution. Therefore, it is more meaningful to improve Si-based negative electrode materials without reducing the theoretical specific capacity. Binders, as inactive additives in silicon-based negative electrode materials, can ensure the close connection of active substances, conductive agents, and current collectors, and they account for a small proportion in the electrode slurry. Therefore, one of the current directions that researchers are keen on is to deal with the problems caused by the volume expansion of silicon-based materials by designing the structure, composition, and compounding of binders. Traditional binders for silicon-based negative electrodes of lithium-ion batteries are mainly polymer-based materials. This is because the unique long-chain structure of macromolecules can serve as the skeleton of active materials. However, the interaction between long-chain one-dimensional macromolecules and silicon is generated in a point-to-point form. This form produces fewer active sites and weak interactions, and cannot effectively alleviate the severe volume expansion of silicon.

[0005] In order to increase the interaction sites with active substances, two-dimensional materials are often used. The interaction between two-dimensional materials and silicon is generated in the form of point-to-face or face-to-face, which greatly increases the number of active sites and enhances the interaction. Among the many two-dimensional materials, graphene / graphene oxide (GO) has high flexibility and high strength. GO is a hexagonal honeycomb layer structure formed by sp² hybrid bonding of carbon atoms, usually in the form of layered stacking. This structure can provide sufficient stability for the silicon negative electrode while alleviating some volume changes, and can be used as a good binder material. However, GO also has some defects. First, the stacking of sheets to form a stable network structure also brings about low ion transportability between layers. When used in lithium-ion batteries, it is difficult for lithium ions to be transported through the interlayers of GO. Secondly, based on the protection of the environment and green health, the current design of silicon-based negative electrode binders mostly uses water as a solvent, and GO has poor dispersibility in water, which will lead to uneven dispersion of substances in the electrode material, thereby affecting the cycle performance of the battery. On the other hand, although GO as a two-dimensional material has provided a very rich active site for modification, due to the lack of strong interaction with Si, after a long period of reversible cycling, the connection with Si particles will fail due to the irreversible slip of GO, so it is very necessary to functionalize GO. Summary of the invention

[0006] In order to solve the above problems, the present application provides a lithium-ion battery silicon negative electrode binder based on functionalized sulfonated graphene.

[0007] The present application provides a lithium-ion battery silicon negative electrode binder based on functionalized sulfonated graphene using the following technical solution: In the first aspect, the present application provides a lithium-ion battery silicon negative electrode binder based on functionalized sulfonated graphene, which adopts the following technical solution: A lithium ion battery silicon negative electrode binder based on functionalized sulfonated graphene comprises a composite of sulfonated graphene oxide and silicon powder, wherein the sulfonated graphene raw materials comprise graphene oxide and p-aminobenzenesulfonic acid.

[0008] By adopting the above technical solution, graphene oxide is modified by aminobenzenesulfonic acid, which can firmly anchor the silicon powder composite through strong chemical action to construct a strong mechanical network. In addition, using sulfonated graphene oxide as a binder component can greatly improve the lithium ion diffusion coefficient of the motor and introduce abundant lithium ion transmission channels.

[0009] Preferably, the sulfonated graphene oxide is prepared by the following method: Graphene oxide is mixed with water and then dispersed to obtain a graphene oxide dispersion, p-aminobenzenesulfonic acid is mixed with water and then dispersed to obtain a p-aminobenzenesulfonic acid dispersion, the graphene oxide dispersion is mixed with the p-aminobenzenesulfonic acid dispersion, heated in a water bath in a sealed environment, the precipitate is washed, excess p-aminobenzenesulfonic acid is removed, and freeze-dried to obtain sulfonated graphene oxide.

[0010] Preferably, the silicon powder composite comprises citric acid and silicon powder.

[0011] By adopting the above technical solution, the silicon powder composite is prepared by the following method: The silicon powder is mixed with water and subjected to ultrasonic treatment to obtain a silicon powder dispersion. Citric acid is added to the silicon powder dispersion and stirred to obtain a silicon powder composite.

[0012] Preferably, the silicon powder is coated with citric acid. The introduction of citric acid can increase the active functional groups on the surface of the silicon powder particles, thereby improving the active sites on the surface of the silicon powder particles, strengthening the interaction between the silicon powder complex and the sulfonated graphene oxide, and further improving the overall stability of the system.

[0013] In a second aspect, the present application provides a method for preparing a lithium-ion battery silicon negative electrode binder based on functionalized sulfonated graphene, using the following technical solution: A method for preparing a lithium-ion battery silicon negative electrode binder based on functionalized sulfonated graphene comprises the following steps: The sulfonated graphene oxide is added to the silicon powder composite, stirred to obtain a mixed solution, and the mixed solution is freeze-dried to obtain a binder.

[0014] After combining the sulfonated graphene with the silicon powder composite, the sulfonated graphene can effectively act as a two-dimensional binder to anchor the silicon particles, thereby further improving the overall stability of the system and reducing the irreversible slip of silicon particles when they are subject to severe volume effects during the cycle process.

[0015] Preferably, the mass ratio of the sulfonated graphene oxide to the citric acid treated silicon powder is 4:1.

[0016] In summary, the present application includes at least one of the following beneficial technical effects: 1. In this application, two-dimensional sulfonated modified graphene oxide is used as a silicon negative electrode binder for lithium-ion batteries, which provides abundant point-to-plane or plane-to-plane connections with silicon powder particles, and flexibly adapts to the system expansion of silicon powder particles during charging and discharging. In addition, p-aminobenzenesulfonic acid is used to functionally modify graphene oxide, thereby improving the dispersibility of graphene oxide and increasing the defects (holes or edges) in the graphene oxide structure, providing more channels for the transmission of lithium ions, thereby improving the electrochemical stability, cycle stability and lithium ion transmission capacity of the battery; 2. Citric acid-assisted sulfonated graphene oxide produces a stronger interaction with silicon powder particles, which is beneficial to the long-term cycle of the battery and helps maintain a stable state during the lithium ion transmission process of the battery.

[0017] 3. The preparation process of this application is simple, and the preparation is green and pollution-free, which provides reference value for the application of two-dimensional materials in battery binders. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 RAMAN spectra and XRD spectra of graphene oxide and sulfonated graphene oxide.

[0019] Figure 2 are TEM images of sulfonated graphene oxide and Example 1.

[0020] Figure 3 It is the infrared spectrum of sulfonated graphene, Example 1 and Example 4.

[0021] Figure 4 It is a diagram showing the electrode peeling test results of Example 1, Example 3 and Example 4.

[0022] Figure 5 is Z' and ω of Example 1 and Example 2 -1 / 2 Linear graph.

[0023] Figure 6 It is a graphical representation of the GITT test curve of the electrode of Example 1.

[0024] Figure 7 is the Li of different electrodes under the discharge state of Example 1 and Example 2 + Graph of the diffusion coefficient.

[0025] Figure 8 is the Li of different electrodes under the charging state of Example 1 and Example 2 + Graph of the diffusion coefficient.

[0026] Fig. 9 It is a graphical representation of the electrode EIS curves of Example 1 and Example 2.

[0027] Fig.10 The electrodes of Example 1 and Example 2 are 1Ag -1 Graph showing 400 cycle performance at a current density of . DETAILED DESCRIPTION

[0028] The present application is further described in detail below with reference to the embodiments: Raw materials description: All raw materials in the examples can be obtained commercially; Preparation Example 1 Preparation of sulfonated graphene oxide: 50 mg of graphene oxide was dispersed in 50 mL of ultrapure water and ultrasonically dispersed for 10 min to obtain graphene oxide dispersion. 500 mg of p-aminobenzenesulfonic acid was added to 50 mL of anhydrous ethanol and stirred until p-aminobenzenesulfonic acid was completely dispersed to obtain p-aminobenzenesulfonic acid dispersion. The graphene oxide dispersion and p-aminobenzenesulfonic acid dispersion were mixed in a round-bottom flask and sealed, heated in a water bath at 95 ° C for 7 h, and then the precipitate formed in the original flask was washed by centrifugation with ultrapure water to remove excess p-aminobenzenesulfonic acid. The washed material was frozen in an ultra-low temperature refrigerator at -75 ° C for 5 h, and sulfonated graphene oxide was obtained after freeze drying.

[0029] Preparation of silica powder composite: 80 mg of silicon powder particles were ultrasonically dispersed in 30 mL of ultrapure water to obtain a silicon powder dispersion, and then 10 mg of citric acid was added to the silicon powder dispersion and stirred for 3 hours to obtain a silicon powder composite.

[0030] Preparation of silicon negative electrode binder for lithium-ion batteries: The prepared sulfonated graphene oxide was added to the silicon powder composite with a mass ratio of 4:1. The mixture was stirred for 3 hours to obtain a mixed solution. The mixed solution was transferred to an ultra-low temperature refrigerator and freeze-dried at -75°C for 5 hours to obtain a silicon negative electrode binder for lithium-ion batteries.

[0031] Preparation Example 2 Preparation Example 2 is based on Preparation Example 1. In Preparation Example 2, when preparing the lithium-ion battery silicon negative electrode binder, the sulfonated graphene oxide is replaced with ordinary graphene oxide.

[0032] Preparation Example 3 Preparation Example 3 is based on Preparation Example 2. In Preparation Example 3, when preparing the silicon negative electrode binder for lithium-ion batteries, citric acid is not added to the silicon powder composite, but is replaced with an equal amount of silicon powder.

[0033] Preparation Example 4 Preparation Example 4 is based on Preparation Example 1. In Preparation Example 4, when preparing the silicon negative electrode binder for lithium-ion batteries, citric acid is not added to the silicon powder composite, but is replaced with an equal amount of silicon powder.

[0034] Example 1 The lithium ion battery silicon negative electrode binder prepared in Preparation Example 1 and conductive carbon black were mixed in ultrapure water at a mass ratio of 9:1, and a uniform slurry was obtained after sufficient stirring. The uniform slurry was applied on a copper foil using a rubber scraper and dried in a vacuum environment at 80°C for 8 hours to obtain an electrode sheet containing a binder.

[0035] Example 2 Example 2 is based on Example 1. In Example 2, the lithium ion battery silicon negative electrode binder of Preparation Example 1 is replaced by the lithium ion battery silicon negative electrode binder of Preparation Example 2.

[0036] Example 3 The lithium ion battery silicon negative electrode binder prepared in Preparation Example 3 and conductive carbon black were mixed in ultrapure water at a mass ratio of 8:1, and a uniform slurry was obtained after sufficient stirring. A rubber scraper was used to apply the uniform slurry on a copper foil, and the mixture was dried in a vacuum environment at 80°C for 8 hours to obtain an electrode sheet containing a binder.

[0037] Example 4 Example 4 is based on Example 3. In Example 4, the lithium ion battery silicon negative electrode binder of Preparation Example 3 is replaced by the lithium ion battery silicon negative electrode binder of Preparation Example 4.

[0038] Performance testing The samples of Examples 1-4 were subjected to the following performance tests: Electrochemical performance test: The electrode sheet was punched into a circular electrode sheet with a diameter of 12 mm, and lithium metal foil was used as the counter electrode. The electrolyte was 0.9 MLiPF6 (EC+DMC 98 vol%, FEC 10 vol%, VC 2 vol%), and Celgard 2400 was used as the separator. CR2032 button-type batteries were assembled in a glove box filled with argon (water and O2 were less than 0.1 ppm). The assembled battery was left to stand for 24 hours before testing. The electrochemical impedance spectroscopy (EIS, 0.01Hz ~100 kHz) test was carried out on a CHI660E electrochemical workstation. The battery was subjected to constant current charge and discharge (GCD) tests on the NEWARE battery test system. The battery was tested using the constant current intermittent titration technique (GITT) on the NEWARE battery test system with a voltage range of 0.005~1.2 V, a relaxation time of 30 min, and a current density of 0.5 A g -1 , and cycle the battery 5 times to activate it before testing.

[0039] Test results see Figure 1-Figure 10 .

[0040] Reference Figure 1 In the spectrum of RAMAN, 1364 cm -1 The Raman peak nearby corresponds to the D peak of graphene, representing the defects in the carbon material lattice. -1 The G peak near the carbon 2Bond structure signal. Their intensity ratio (ID / IG) indicates the defect information of carbon materials. The larger the ID / IG, the more defects there are inside the material. As shown in the figure, the ID / IG value of sulfonated graphene oxide (2.17) is higher than that of graphene oxide (1.58), which indicates that the sulfonation process introduces more structural defects, such as edges and holes, into the graphene oxide flakes.

[0041] Reference Figure 1 In the XRD spectrum, the diffraction peaks of the XRD spectrum of p-aminobenzenesulfonic acid standard are located at 12.7°, 18.1°, 23.6° and 25.6°, corresponding to its crystal planes (020), (111), (200) and (131), respectively. The XRD spectrum of graphene oxide has a diffraction peak at 10.6°, representing the (001) crystal plane of carbon. The XRD spectrum of SGO shows a diffraction peak of the carbon crystal plane (001) at 10.3°. The calculated intercrystalline spacings of graphene oxide and sulfonated graphene oxide are 0.83 nm and 0.86 nm, respectively. The crystal space expansion of graphene oxide after sulfonation indicates that the graphene sheets grafted with p-aminobenzenesulfonic acid groups have a smaller stacking tendency.

[0042] Reference Figure 2 The microstructure of sulfonated graphene oxide and Example 1 was observed by transmission electron microscopy (TEM). The morphology of sulfonated graphene oxide flakes was not smooth, the edges were rough, and there were some holes in the layer. Figure 1 From the results of the RAMAN image in Figure 2, it can be considered that the sulfonation modification process introduced many defects in the form of pores and edges into the graphene oxide layer.

[0043] Reference Figure 3 and Figure 4In the infrared spectrum, compared with the sulfonated graphene not compounded with silicon powder particles, the displacement of the CO (1725 cm-1) and CC (1579 cm-1) peaks of Example 4 is negligible, indicating that there is no strong reaction between silicon powder particles and sulfonated graphene oxide. The addition of citric acid causes the characteristic peaks of CO (1701 cm-1) and CC (1586 cm-1) in Example 1 to shift compared with sulfonated graphene oxide, indicating that ester bonds are formed between silicon powder particles and citric acid and sulfonated graphene, respectively. The confirmation of the strong chemical interaction between sulfonated graphene and citric acid, and between silicon powder particles and citric acid shows that citric acid molecules tend to form a covering layer on silicon powder particles, and the auxiliary functional sulfonated graphene oxide can effectively anchor silicon powder particles as a two-dimensional binder. In the graph of the electrode peeling test results, the untreated graphene oxide has almost no ability to bind to silicon powder particles, while the sulfonated graphene oxide shows excellent silicon electrode binding effect. This is because sulfonated graphene oxide has better dispersibility and richer defects and edges than graphene oxide, introducing more active sites. The excellent adhesion of sulfonated graphene oxide fully demonstrates the great potential of graphene oxide-based two-dimensional materials as electrode binders. Under the synergistic effect of citric acid, the peel strength of the anode of Preparation Example 1 increased to 45.4 N m -1 This is because the introduction of citric acid can increase the active functional groups on the surface of silicon powder particles, that is, increase the active sites on the surface of silicon powder particles and strengthen the interaction between sulfonated graphene oxide and silicon powder particles.

[0044] The σ value is calculated based on the results of the first impedance test of the battery. Since the lithium ion diffusion coefficient is inversely proportional to the σ value, the size of the lithium ion diffusion coefficient can be judged by comparing the σ value. Figure 5 It can be seen that the σ value of the electrode in Example 1 is much smaller than that of the electrode in Preparation Example 2, which indicates that the lithium ion diffusion rate induced by sulfonated graphene oxide is much higher.

[0045] Combination Figure 5 and Figure 6 , Figure 6 The battery was cycled for 5 cycles at a current density of 0.5 a g-1 and then subjected to a GITT test with a relaxation time of 30 min and a pulse time of 20 min. The graph shows that the sulfonated graphene oxide binder significantly increased the lithium ion diffusion coefficient of the electrode by nearly an order of magnitude. This is because the -SO3- in the sulfonic acid group induces a lithium ion transport path enriched in the sulfonated graphene oxide binder.

[0046] Combination Figures 6 to 8 The lithium ion diffusion coefficient of the electrode in Example 2 varies from 2.4×10 -11 cm 2 s -1~1.1×10 -9 cm 2 s -1 The lithium ion diffusion coefficient during charging varies from 1.3×10 -12 cm 2 s -1 ~1.6×10 -10 m 2 s -1 The lithium ion diffusion coefficient of the electrode in Example 1 varies in the range of 5.2×10 -11 cm 2 s -1 ~7.8×10 -9 cm 2 s -1 The lithium ion diffusion coefficient during charging varies from 7.0×10 -13 cm 2 s -1 ~ 6.0 × 10 -10 cm 2 s -1 This shows that the dispersibility and more defects (including edges or holes) brought by sulfonation of graphene oxide can effectively alleviate the steric hindrance of graphene oxide sheets to lithium ions, thereby further improving the diffusion efficiency of lithium ions.

[0047] Combination Fig. 9 The charge transfer impedance of the electrode in Example 1 (41.13Ω) is much lower than that of the electrode in Example 2 (107.7Ω), which indicates that the sulfonation of graphene significantly improves the conductivity of the material.

[0048] Combination Fig.10 After 50 cycles, the capacity of the electrode of Example 2 decreased rapidly, while the electrode of Example 1 showed excellent cycle stability after 60 cycles, and maintained a reversible specific capacity of 1590 mA h g-1 even after 400 cycles (compared with 50 cycles, the capacity retention rate was 68.6%). After two cycles, its average Coulombic efficiency was about 99.4%, showing the excellent electrode performance produced by this design.

[0049] Combined with the above image analysis, it can be seen that the sulfonated graphene binder can improve the dispersibility of graphene oxide and provide more channels for lithium ion transmission for graphene oxide. At the same time, the addition of citric acid can strengthen the interaction with Si, so that the battery can maintain a stable state during long-term cycling and lithium ion transmission.

[0050] This specific embodiment is only an explanation of the present application, and it is not a limitation of the present application. Through the above description, relevant staff can make various changes and modifications without deviating from the technical idea of ​​the present application. The technical scope of the present application is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A lithium-ion battery silicon negative electrode binder based on functionalized sulfonated graphene, characterized in that: The invention comprises a composite of sulfonated graphene oxide and silicon powder, wherein the sulfonated graphene raw material comprises graphene oxide and p-aminobenzenesulfonic acid.

2. A lithium ion battery silicon negative electrode binder based on functionalized sulfonated graphene according to claim 1, characterized in that: The sulfonated graphene oxide is prepared by the following method: Graphene oxide is mixed with water and then dispersed to obtain a graphene oxide dispersion, p-aminobenzenesulfonic acid is mixed with water and then dispersed to obtain a p-aminobenzenesulfonic acid dispersion, the graphene oxide dispersion is mixed with the p-aminobenzenesulfonic acid dispersion, heated in a water bath in a sealed environment, the precipitate is washed, excess p-aminobenzenesulfonic acid is removed, and freeze-dried to obtain sulfonated graphene oxide.

3. The lithium-ion battery silicon negative electrode binder based on functionalized sulfonated graphene according to claim 1, characterized in that: The silicon powder compound comprises citric acid and silicon powder.

4. A lithium ion battery silicon negative electrode binder based on functionalized sulfonated graphene according to claim 4, characterized in that: The silicon powder composite is prepared by the following method: The silicon powder is mixed with water and subjected to ultrasonic treatment to obtain a silicon powder dispersion. Citric acid is added to the silicon powder dispersion and stirred to obtain a silicon powder composite.

5. A method for preparing a lithium ion battery silicon negative electrode binder based on functionalized sulfonated graphene according to any one of claims 1 to 3, characterized in that: The steps include: The sulfonated graphene oxide is added to the silicon powder composite, stirred to obtain a mixed solution, and the mixed solution is freeze-dried to obtain a binder.

6. The lithium-ion battery silicon negative electrode binder based on functionalized sulfonated graphene according to claim 4, characterized in that: The mass ratio between the sulfonated graphene oxide and the citric acid treated silicon powder is 4:1.